Project-Based Learning in Building Pancasila Student Ideology - Eneng Sumarni; Siti Rahmawati; Cecep Hilman (P3M IAI Nusantara Batang Hari, 2023)
Curriculum is a guideline for the continuity of an education with a view to achieving good learning goals and objectives. An independent curriculum is a learning plan that is made to feel fun, active and pressure-free learning activities to be able to bring out the natural talents that exist in students. The characteristics of an independent curriculum are developing character according to Pancasila values by implementing project based learning. This study uses an analytical method that is library research, namely library-based research. From the results of the analysis, the project-based learning model is one of the planning lessons that can be an effort to realize students with character according to the profile of Pancasila students. Activities carried out based on learning projects are related to forming students according to the 6 dimensions in the Pancasila student profile, namely faith and devotion to God, global diversity, mutual cooperation, critical reasoning, independence and creativity. This character has a relationship that can be realized with the habit of applying the PjBL model to learning at school.